Calorie intake and short-term survival of critically ill patients. Issue 2 (April 2019) - Hartl, Wolfgang H.; Bender, Andreas; Scheipl, Fabian; Kuppinger, David; Day, Andrew G.; Küchenhoff, Helmut
Summary: Background & aims: The association between calorie supply and outcome of critically ill patients is unclear. Results from observational studies contradict findings of randomized studies, and have been questioned because of unrecognized confounding by indication. The present study wanted to re-examine the associations between the daily amount of calorie intake and short-term survival of critically ill patients using several novel statistical approaches. Methods: 9661 critically ill patients from 451 ICUs were extracted from an international database. We examined associations between survival time and three pragmatic nutritional categories (I: <30% of target, II: 30–70%, III: >70%) reflecting different amounts of total daily calorie intake. We compared hazard ratios for the 30-day risk of dying estimated for different hypothetical nutrition support plans (different categories of daily calorie intake during the first 11 days after ICU admission). To minimize indication bias, we used a lag time between nutrition and outcome, we particularly considered daily amounts of calorie intake, and we adjusted results to the route of calorie supply (enteral, parenteral, oral). Results: 1974 patients (20.4%) died in hospital before day 30. Median of daily artificial calorie intake was 1.0 kcal/kg [IQR 0.0–4.1] in category I, 12.3 kcal/kg [9.4–15.4] in category II, and 23.5 kcal/kg [19.5–27.8] in category III. When compared to a plan providing daily minimal amounts of calories (category I), the adjusted minimal hazard ratios for a delayed (from day 5–11) or an early (from day 1–11) mildly hypocaloric nutrition (category II) were 0.71 (95% confidence interval [CI], 0.54 to 0.94) and 0.56 (95% CI, 0.38 to 0.82), respectively. No substantial hazard change could be detected, when a delayed or an early, near target calorie intake (category III) was compared to an early, mildly hypocaloric nutrition. Conclusions: Compared to a severely hypocaloric nutrition, a mildly hypocaloric nutrition is associated with a decreased risk of death. In unselected critically ill patients, this risk cannot be reduced further by providing amounts of calories close to the calculated target. Study registration: ID number ISRCTN17829198, websitehttp://www.isrctn.org .